A long duration impulse current generator for testing surge arresters in distribution systems - Prasertsang, Chatariya; Triuattanapiruk, Nawakun; Yutthagowith, Peerawut (My University, 2013)
This paper presents development of a long duration impulse current generator for testing surge arresters in distribution systems. The developed generator was designed by hand calculation at the beginning stage, then with the help of EMTP/ATP simulation. The design of the generator circuit parameters (resistors, inductor, and capacitors) is provided in this paper. The effect of internal resistance of an inductor to the current waveform is presented. An approach for adjusting the circuit parameters of the generator to obtain the current waveform accordance with the standard is also proposed. The generated current waveform has met the requirements of IEC standard. The developed long duration current generator was employed to generate current for testing a surge arrester in an HV laboratory. This accomplishment will be useful in test and evaluation of surge arrester performance. © 2013 IEEE.
Keywords: Arrester; Distribution system; Generator; Inductor; Long duration impulse current; Resistor